Analisis Kemampuan Observasi Siswa pada Konsep Perubahan Wujud Benda dan Sifatnya dengan Metode Eksperimen - Paujiah, Nur; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Science learning is learning that appreciates the process. In science learning, you don’t see the final result but only the process of learning. Designing experimental-based learning activities can be one way that can be done to see a process and not only the result. In general, students often know the concept, but students don’t understand the concept. Students understanding of abstract science concepts can be helped by conducting experiments or making observations, where observation is one indicator of process skills. The purpose of this study was to analyze students’ observation skills on the concepts of changing the shape of objects and properties with the experimental method of learning science in the 5th grade of SDN 1 Bojongcae in the 2020/2021 academic year. This research is qualitative research and activity analysis. The subjects in this study were nine fifth graders. The instruments used in this research are field notes, test sheets, and observation sheets which have been adjusted to the students' observation abilities. Observational ability is divided into three indicators, namely the skill of using the senses, the ability to collect relevant facts, and the ability to find similarities and differences. The result of the research analysis of students is observational abilities on the concept of changing the object's shape and properties with experimental methods in science learning fifth-grade SDN 1 Bojongcae have an average value of 74% proportion with good category. These results become the basis for teachers to determine future science learning methods and strategies, especially in online learning.